Absence of visual discrimination by female eastern newts during mate selection. Issue 5 (3rd September 2017) - Spicer, Mackenzie M.; Hart, Shelby L.; Brighty, Sara R.; Gall, Brian G.
Abstract : Male eastern newts ( Notophthalmus viridescens ) exhibit tremendous variation in several characteristics, including the number of dorsal spots, the brightness of those spots, tail depth and tail length. These traits could be used by females for mate selection decisions. We conducted two experiments to determine whether females use visual signals to assess these characteristics in their mate selection decisions by simultaneously exposing a female to males of opposing characteristics. We observed female preference for the number of spots on a male's dorsum, the brightness of male dorsal spots, male body mass, and male tail depth and length. We then recorded the amount of time the female spent in a preference zone adjacent to each of the males. Female newts did not show a significant preference for any of the characteristics observed, spending roughly equal amounts of time in both preference zones. These results, combined with the results of several previous studies, suggest that female eastern newts do not use visual signals to assess these traits in their mate selection decisions. Given that most of these traits are sexually dimorphic, this is likely due to the reproductive advantage created by the intense male–male competition present and their amplexus-based mating system.